Skill improvement of tea bags processing from moringa, gotu kola (Centella asiatica L.), and cocoa leaves - Yunda Maymanah Rahmadewi; Meka Efrianeta; Andhan Dwi Pratiwi; Amita Daniati (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Agriculturalâ€™s potential sometimes have not maximally utilized because of several plants that have health effects such as moringa, pegagan/gotu kola, and cocoa. Communities in Padukuhan Gunungasem, Salaran, and Soka, Ngoro-oro, Patuk, Gunung Kidul still have limited knowledge and skills related to processing these plants. The purpose of this community service were to give counseling about food safety Good Manufacturing Practice (GMP), train the the making of tea bags healthy drinks,and train the packaging and labels of tea bags. The method used was training and hands-on practice. The program implementation team consisted of UAD Food Service Industry UADâ€™s lecturer and Public Health students. The activity was held in one of the residentsâ€™ house or the village headâ€™s house. The results of community service were the knowledge about food safety increased, skills in making Moringa, â€œpegaganâ€, cocoa leaf teabags and in packaging and making tea bag labels also increased.